Intersubjectivity and poetic translation - Ramalho Almeida, Paula (POLISSEMA – Revista de Letras do ISCAP, 2019)
No one will deny the challenges of translating poetry. But it is not as clear why we should consider, in general terms, the translation of any prose easier than the translation of verse. Good prose does not differ substantially from good verse, as Wordsworth insisted in his 1802 “Preface to Lyrical Ballads”. Of course, there are often more elements to consider in verse composition: the expression form is indeed of more significance in verse than in prose, for the creation of meaning in the former is concentrated into smaller units or, in essence, depends on the expression- form itself. The pleasure of reading and writing poetry derives from precisely this dependence on the signifier, on words rather than ideas, as Mallarmé would put it. We may conclude that the translative process is the same in both modes of literary translation, due to the poetic function’s manifest prevalence in literary texts, even if the type of effort varies, as we will see, according to the level of abstraction the poem presents. And this is where the concept of intersubjectivity – as well as the awareness thereof – takes on a whole new outlook. Despite what it may seem at first glance, the presence of intersubjectivity is far from being a given truth, and it is likely that many translators would benefit from integrating it into their work.